Building destination resilience in the tourism disaster management process from the past experiences: The case of the 2018 Hokkaido Eastern Iburi earthquake in Japan. Issue 5 (2nd November 2022) - Chan, Chung-Shing; Nozu, Kazuo; Zhou, Qinrou
ABSTRACT: This exploratory research reports the perception of local tourism stakeholders towards the distinctive contribution of tourism to the disaster management process and the destination resilience across the pre-to-post period of the September 2018 Hokkaido Eastern Iburi earthquake in Japan through a series of in-depth interviews with 15key informants in summer 2019. The qualitative content analysis identifies, firstly, the multi-functionality of tourism resources, spaces and industries for disaster preparation. Secondly, it points out that information and communication barriers are the major difficulties to be tackled, especially in a complicated situation involving different people and problems during prodromal and emergency phases. The study reveals that post-disaster recovery may lead to new product creation, image improvement, local knowledge enrichment, people-to-people and people-to-place connections, which facilitate sustainable tourism development with long-term vision and strategy. The research concludes that the strengthened destination resilience must be achieved through an effective collaboration among local stakeholders including public sector, private sector and other non-governmental or community-based organizations.